2022
DOI: 10.3390/v14030617
|View full text |Cite
|
Sign up to set email alerts
|

Avidity of IgG to SARS-CoV-2 RBD as a Prognostic Factor for the Severity of COVID-19 Reinfection

Abstract: The avidity index (AI) of IgG to the RBD of SARS-CoV-2 was determined for 71 patients with a mild (outpatient) course of COVID-19, including 39 primarily and 36 secondarily reinfected, and 92 patients with a severe (hospital) course of COVID-19, including 82 primarily and 10 secondarily infected. The AI was shown to correlate with the severity of repeated disease. In the group of outpatients with a mild course, the reinfected patients had significantly higher median AIs than those with primary infections (82.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Nevertheless, median RAI values were at a comparably low level during the whole study period. These findings are in line with those of other research groups, showing an incomplete avidity maturation pattern of SARS-CoV-2 IgG antibodies after natural infection [32][33][34]. In contrast, Struck et al show that two vaccination steps or the combination of vaccination and natural infection lead to the establishment of high avidity anti-SARS-CoV-2 IgG antibodies [34].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, median RAI values were at a comparably low level during the whole study period. These findings are in line with those of other research groups, showing an incomplete avidity maturation pattern of SARS-CoV-2 IgG antibodies after natural infection [32][33][34]. In contrast, Struck et al show that two vaccination steps or the combination of vaccination and natural infection lead to the establishment of high avidity anti-SARS-CoV-2 IgG antibodies [34].…”
Section: Plos Onesupporting
confidence: 91%
“…The study of Manuylov et al recently showed that the avidity of anti-SARS-CoV-2 IgG antibodies can be used as a prognostic factor for the severity of COVID-19 reinfection. A low avidity index (� 40%) following the initial infection enhances the risk of a severe COVID-19 course in case of SARS-CoV-2re-infection significantly [32].…”
Section: Plos Onementioning
confidence: 99%
“…In a previous study [ 31 ], this reduced neutralizing antibody response was observed when these same samples were tested for the alpha (B.1.1.7), beta (B.1.351), and gamma (P.1) variants and was ascribed to the substantial divergence between the infecting strain (wt) and the variants tested. The reduction in neutralizing activity against Omicron and other VoCs was probably due to low affinity, and therefore low avidity, antibodies, confirming that only high-avidity antibodies are involved in virus neutralization, since they can effectively compete with angiotensin-converting enzyme 2 (ACE2) for binding to the RBD [ 11 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, stronger avidity maturation was associated with disease resolution. Finally, Manuylov et al presented data that indicated that the presence of low‐avidity IgG to RBD during reinfection is a negative prognostic factor, in which a patient's risk of developing COVID‐19 in a severe form is significantly increased 32 . Therefore, though it is certainly not possible to exclude future SARS‐CoV‐2 infection based on the presence of high avidity IgG directed towards RBD, the lack of high avidity IgG despite vaccination might be regarded as an indication of potential risk.…”
Section: Introductionmentioning
confidence: 99%